2018
DOI: 10.1089/fpd.2018.2441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Grower-Friendly, Science-Based Sampling Approaches for the Detection ofSalmonellain Ponds Used for Irrigation of Fresh Produce

Abstract: The recognition that irrigation water sources contribute to preharvest contamination of produce has led to new regulations on testing microbial water quality. To best identify contamination problems, growers who depend on irrigation ponds need guidance on how and where to collect water samples for testing. In this study, we evaluated several sampling strategies to identify Salmonella and Escherichia coli contamination in five ponds used for irrigation on produce farms in southern Georgia. Both Salmonella and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…Water samples collected for filtration in ponds were collected from banks of the pond. Other research has shown that location of water collection from within pond sites can affect the quantitative recovery of Salmonella and E. coli [30,31].…”
Section: Plos Onementioning
confidence: 99%
“…Water samples collected for filtration in ponds were collected from banks of the pond. Other research has shown that location of water collection from within pond sites can affect the quantitative recovery of Salmonella and E. coli [30,31].…”
Section: Plos Onementioning
confidence: 99%
“…For biological indicators, generic E. coli, fecal coliforms, total coliforms, enterococci, and aerobic/heterotrophic bacterial plate counts have been compared to Salmonella presence/absence and concentrations. A few studies have identified a predictive relationship between the levels of generic E. coli and the probability of detecting Salmonella [81,82,87,100], while others have not seen this relationship [78,80,88]. The same dichotomy was seen with the other biological indicators [78,80,83,87,91,92,98,100].…”
Section: Salmonellamentioning
confidence: 98%
“…Most studies in the U.S. have focused on the East and West Coasts in areas where agricultural production is high. Along the East Coast, Salmonella prevalence ranges between 3% and 100% [4,5,8,40,[77][78][79][80][81][82][83][84][85][86][87]. Most studies on the West Coast have been performed in CA, where prevalence ranges from 6% to 65% [6,[88][89][90][91].…”
Section: Salmonellamentioning
confidence: 99%
See 2 more Smart Citations